A fronteira meridional do Império do Brasil: Segurança, ameaça e política externa no século XIX (1850-1889) (TEL Tempo, Espaço e Linguagem, 2025)
Abstract: The southern border of the Brazilian Empire was a space where security and sovereignty were constantly negotiated and justified through the discursive construction of threat. Imperial foreign policy used the rhetoric of instability to legitimize military and diplomatic interventions in the Río de la Plata region, consolidating Brazil’s presence. The research adopts an interdisciplinary approach, combining documentary analysis with concepts from International Relations History and International Security Studies to understand the interaction between discourse and power in imperial foreign policy.Keywords: Brazilian Empire. Southern border. Security. Threat construction. Foreign policy.